Mengatasi Timbulan Sampah Pasca Hari Raya Keagamaan di Bali Melalui Edukasi Berbasis Ekoteologi: Peran Strategis Kantor Wilayah Kementerian Agama Provinsi Bali - Oka Ariartha, Ida Bagus (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
This policy paper examines the issue of increased post-religious holiday waste generation in Bali Province, which causes negative environmental and social impacts, focusing on low public awareness and behavior in responsible waste management. The root cause is identified as the scarcity of effective, contextual, and integrated education and socialization regarding specific holiday waste management, particularly due to the insufficient involvement of religious counselors and community leaders in campaigning for waste management aligned with spiritual and ecological values. The approach employed in developing this policy paper involves a qualitative analysis of secondary data, including policy documents, regulations, and academic articles, complemented by the Urgency, Seriousness, Growth (USG) method for problem prioritization and William N. Dunn's criteria for policy alternative selection. The analysis indicates that a policy alternative involving the issuance of a Circular Letter by the Head of the Bali Provincial Office of the Ministry of Religious Affairs—concerning Guidelines for Ecotheology Implementation in Environmental Governance & Waste Management at Places of Worship—emerged as the strategic choice, achieving the highest evaluation score. It is therefore recommended that the Head of the Bali Provincial Office of the Ministry of Religious Affairs issues this Circular Letter to encourage and guide managers of places of worship in establishing internal waste management units, providing adequate waste sorting facilities, integrating ecotheological messages into religious sermons, processing organic waste independently or collaboratively, and periodically reporting their waste management efforts, as part of implementing the Ministry's Ecotheology priority program and supporting the Bali Clean Waste Movement.